Penelitian Lingkungan Pantai Wilayah Pesisir Kabupaten Cirebon, Jawa Barat - Prijantono Astjario (Pusat Survei Geologi, 2006)
Nowadays, natural resources in Indonesia have been decreased because of the rapid increase in development and human population. It is most likely that marine resources will become a primary source in supporting our economics in the future. Marine and coastal zones seem to become areas of our main priority for industrial, agrobusiness, agroindustrial, settlement, tourism, transportation and harbour developmen. However, these areas are still having various problems or cases which couId cause their unoptimum development and managements.The decrease of seawater quality standard caused by high suspended polluted by solid and Iiquid waste, sea water intrusions, abrations and accretions, shoalings, floods, and dryness are some of the various cases which can be found in the marine and coastaI zones. Another case which is not less important is human behaviour who have destructed mangroves and changed the function of swampy forest to become fishpond areas. The survey in the marine and coastaI areas, especially in the eastern coast of the Cirebon regency, aims to obtain data, in which these cases are potentially found by applying the coastal characteristic observation and remote sensing methods.